The Influence of Islamic Religious Education (PAI) on Students' Mathematical Logical Thinking Skills in Junior High School - Al Ayyubi, Ibnu Imam; Nurhikmah; Eko Prayetno; Tiara Annastasya; Siti Rahmawati (International Journal of Education Management and Religion, 2025)
This study aims to determine the effect of learning in Islamic Religious Education (PAI) on students' mathematical logical thinking abilities at SMP Roudlotul ‘Ulum, Parongpong, West Bandung, under the Roudlotul ‘Ulum Islamic Boarding School Foundation. The population consisted of all students at SMP Roudlotul ‘Ulum, with a sample of 28 ninth-grade students. The research employed a quantitative explanatory research approach. The sampling technique used was probability sampling with simple random sampling, and the instruments included validated and reliable questionnaires and tests. The normality test results showed that the data were normally distributed with a significance value of 0.200. Correlation analysis indicated a very strong relationship between PAI learning and students' mathematical logical thinking abilities, with a correlation coefficient of 0.817 and a significance value of 0.000. Regression analysis revealed a determination coefficient of 71.4%, meaning that PAI learning contributed 71.4% to students' mathematical logical thinking abilities, while the remaining 28.6% was influenced by other factors. The linear regression equation Y=0.473+0.816XY = 0.473 + 0.816XY=0.473+0.816X indicates that each one-unit increase in PAI learning improves mathematical logical thinking ability by 0.816. These findings show that PAI learning not only builds students' religious character but also supports the development of their mathematical logical thinking abilities. Thus, it is essential for educators to implement integrative and holistic learning approaches.